Influência da proteção superficial na liberação de flúor e propriedades mecânicas de cimentos de ionômero de vidro: revisão sistemática e meta-análise - Lopes, Davi Faria (2021)
Glass ionomer cement (GIC) has been widely used in pediatric dentistry as a definitive restorative material due to its main properties of chemical bonding to enamel and dentin and fluoride release. Due to the long setting time and sensitivity to water loss (syneresis) and gain (imbibition) during this period, surface coating agents have been suggested to isolate restorations from contact with saliva until the final setting of the GIC. However, it is still unclear in the literature whether the effect of using these surface coating agents on the properties of GICs. Thus, this systematic review of laboratory studies aimed to evaluate the effect of surface coating agents on fluoride release, microhardness, and strength of conventional glass ionomer cements. Studies were identified from a systematic search in PubMed, Web of Science, and Scopus databases. Two reviewers independently selected the studies; one reviewer extracted the data and assessed the risk of bias. The resulting data were meta-analyzed using a randomeffects model, with a significance level of p < 0.05. Heterogeneity (I2) was assessed using Cochran's Q test. Of the 1595 potential studies, 26 eligible studies were identified with fluoride release, microhardness, or strength data. Surface coating agents significantly reduced the fluoride release (Z=9.62; p<0.00001) and microhardness (Z = 2.77; p=0.006), and had no effect on strength (Z=0.91; p=0.36). Most of the studies presented a high risk of bias. Based on the results found, it can be concluded that surface coating agents do not improve the mechanical properties of glass ionomer cement and impair fluoride release.